Respostas

A melhor resposta!
2013-07-28T17:02:19-03:00
-x² + 6x - 5 = 0
a=-1
b=6
c=-5

Delta=6²-4*(-1)*(-5)
Delta=36-20
Delta=16

x'=-6+V16/2*(-1)
x'=-6+4/-2
x'=-2/-2
x'=1

x''=-6-V16/2*(-1)
x''=-6-4/-2
x''=-10/-2
x''=5

Observação: V significa raiz quadrada e * significa multiplicação.
4 5 4
2013-07-28T17:02:33-03:00
X= -b+- Vb²-4ac
          2a
x= -6 +- V6²-4.-1.-5
            2.-1
x= -6 +- V36-20
            -2
x= -6 +- V16                x' = -6 - 4                       x'' = -6 + 4
           -2                              -2                                   -2

                                    x' = 5                              x'' = 1

1 5 1